Efficiency of Electronic Devices for Unsteady Flow of Failures - Eidukas, D.; Stupak, V. (Elektronika ir Elektrotechnika, 2011)
Electronic devices inspected by using built-in test equipment are analyzed. The method of calculation of efficiency of devices for a case of unsteady Poisson flow of failure is offered. The method is based on estimation of the bottom and top limits for values of efficiency on analyzed interval of exploitation. For this purpose, efficiency of devices for corresponding Poisson flows of failures is calculated. A relative error of definition of efficiency value is defined. As an estimation of an error, its maximal value is used. Computing experiment according to the given error is executed. Experiment considers really possible values of the parameters influencing efficiency of the device. Results of experiment show that the maximal relative error of an estimation of a parameter of efficiency does not exceed 6.5 % . Bibl. 9, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.287